HAK WARIS ANAK ANGKAT MENURUT HUKUM ISLAM DI INDONESIA - Suharto Suharto (Faculty of Sharia and Law UNISNU Jepara, 2014)
This article aims to discuss the inheritance rights of adopted children based on the view of Islamic law in Indonesia. There are three results of this library research; 1) the adopted child whose maintenance responsibility of everyday life, including the cost of living, health care costs, education costs, and so forth switches from biological parents to the adoptive parents. In addition, adopted children's lineage is not disconnected from biological parents. They do not inherit each other.2) Besides fulfilling the requirements specified in the legislation, legality of adopted children, should also be based on the determination of the Religious Court. 3) Inheritance right of adopted children is obtained through the wajibah escrow agency, and maximum amount is 1/3 (one third) of his adoptive parents legacy.Keywordsinheritance right, adopted children, parent, Islamic law Artikel ini bertujuan untuk membahas hak waris anak angkat dalam pandangan hukum Islam di Indonesia. Ada tiga hasil studi pustaka ini;1) anak angkat adalah anak yang pemeliharaan tanggung jawab kehidupan sehari-harinya, termasuk biaya hidup, biaya kesehatan, biaya pendidikan, dan sebagainya beralih dari orang tua biologis kepada orang tua angkatnya. Selain itu, nasab anak angkat tidak terputus dari orang tua kandungnya dan mereka tidak saling mewarisi. 2) Legalitas anak angkat, selain harus memenuhi persyaratan yang ditentukan dalam undang-undang juga harus didasarkan pada penetapan Pengadilan Agama. 3) Warisan hak anak angkat diperoleh melalui agen wasiat wajibah, dengan jumlah maksimum adalah 1/3 (sepertiga) dari warisan orang tua angkat tuanya.